2016
DOI: 10.1080/03014460.2016.1224386
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between different nutritional anthropometric statuses and health-related fitness of South African primary school children

Abstract: Background: A double burden of both under- and over-nutrition exists among South African children. Aim: To describe associations between nutritional statuses and health-related fitness test performances. Subjects and methods: Height and weight of 10 285 children (6–13 years; n = 5604 boys and 4681 girls) were measured and used to calculate body mass index (BMI) and prevalence of overweight and obesity, stunting, wasting and underweight. Physical fitness scores for standing long jump, shuttle run, sit-and-reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 38 publications
(67 reference statements)
6
28
3
Order By: Relevance
“…Muscular power of the lower limb. Lower limb explosive power was evaluated by a long jump test [17,18,20,21,23,25,33,34,36,37]. The validity and reliability of jump tests have been previously evaluated in children by several authors [31,32,38].…”
Section: Physical Fitnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Muscular power of the lower limb. Lower limb explosive power was evaluated by a long jump test [17,18,20,21,23,25,33,34,36,37]. The validity and reliability of jump tests have been previously evaluated in children by several authors [31,32,38].…”
Section: Physical Fitnessmentioning
confidence: 99%
“…Flexibility. Hip and low back flexibility were evaluated by the Sit & Reach test [17,18,20,21,23,25,33,34], whose reliability and validity have been previously assessed in the literature [32,41]. In a seated position with their knees extended and their feet placed firmly against a vertical support, children reached forward along the measuring line as far as possible with their arms at the same level.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…noted that these findings were much higher than the baseline values of 1.2 and 0.2% prevalence of childhood overweight and obesity respectively in 1994 [ 63 ]. Again, Armstrong et.al [ 64 ]. study involving school children aged 6 to 13 years old reported a combined overweight and obesity prevalence of 15.4% (1564/10,285).…”
Section: Resultsmentioning
confidence: 99%
“… 9 , 19 , 20 , 21 , 22 , 23 Previous studies have demonstrated that health-related physical fitness tests and comprehensive evaluations of the health status of the body are important in identifying early risk factors of cardiovascular disease. 21 , 22 , 24 , 25 , 26 , 27 , 28 , 29 However, studies investigating the relationship between stroke and health-related physical fitness are still lacking at this time. To determine the risk factors for stroke and explore the significance of health-related physical fitness testing in stroke prevention, we performed a survey in 627 medical staff members using stroke high-risk population screening and a health-related physical fitness test.…”
Section: Introductionmentioning
confidence: 99%